Disseminated Fusariosis in Immunocompromised Children—Analysis of Recent Cases Identified in the Global Fungiscope Registry. Issue 2 (February 2017) - Hassler, Angela; Lieb, Adrian; Seidel, Danila; Cesaro, Simone; Greil, Johann; Klimko, Nikolay; Khostelidi, Sofya; Solopova, Galina; Ogunc, Dilara; Durán Graeff, Luisa; Cornely, Oliver A.; Vehreschild, Maria J. G. T.; et al.
Abstract : Disseminated fusariosis is a rare disease, and data are scant in pediatric patients. In the FungiScope registry, we identified 10 children with disseminated fusariosis between 2006 and 2015. Our analysis of the largest pediatric case series reported to date adds pediatric-specific experience to the management of this opportunistic infection in children. Abstract : Supplemental Digital Content is available in the text.